(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to evaluate the direct deduction department’s procedures for the process of collecting income tax using the direct deduction method for state departments and the public sector in light of direct deduction tax instructions No. (1) of 2007 and Income Tax Law No. (113) of 1982 (amended) through Giving a clear idea of ​​the reality of tax collection procedures because this type of tax is one of great importance because it contributes to the provision of financial revenues to the state to finance its expenses and direct the economy towards achieving its social, economic and political goals. The researcher makes comparisons between the procedures of the General Tax Authority in collecting the tax and what was approved by the issued instructions and presenting some conclusions and recommendations that could contribute to evaluating the procedures of the Authority in collecting the tax according to this type of tax. Taxes, and the number of the Authority’s employees who are assigned to audit the direct withholding tax for state employees, whose number is (2) employees, as well as the presence of a clear reluctance by the General Authority for Taxes in the field of field audits to ensure that the calculation of the direct withholding tax is correct and to ensure that tax deductions are transferred on time.